Guidance and Training in Digital Financial Bookkeeping for UMKM (MSME) Batik Kantil Malang - Permatasari, Ita Rifiani; Aini, Lilies Nur; Khabibah, Umi; Nurtjahjani, Fullchis; Sinatriya, Jatrifia Ongga; Aini, Yulis Nurul (Transpublika Publisher, 2025)
Financial bookkeeping and accounting systems are essential for small and medium enterprises (SMEs), even at the smallest scale, despite their often-burdensome perception among many traditional business owners. With advances in technology, financial record-keeping can now be digitized. However, UMKM (MSME) Batik Kantil in Malang continues to face challenges due to its reliance on manual bookkeeping, which results in suboptimal financial records. This community engagement activity aims to provide guidance and training in financial bookkeeping using Microsoft Excel. The target participants are the employees of UMKM Batik Kantil in Malang, and the program employs lectures, tutorials, discussions, and hands-on practice as its primary methods. This initiative is designed to equip UMKM practitioners with the skills to analyze real business transactions and compile comprehensive financial reports.